Implementasi Kurikulum Merdeka di MAN 1 Medan - Putri Febby Aulia; Rustam Rustam; Fitri Hayati (Jurnal Budi Pekerti Agama Islam, 2024)
This study is set against the background of the co-19 pandemic which affects many sectors of human life, one of which is the field of education. This pandemic also encourages innovation in the field of education in making updates or changes to the curriculum. In the curriculum changes used now are known as the independent learning curriculum. This study aims to identify and obtain information about the planning, implementation and effectiveness of the implementation of the independent curriculum at MAN 1 Medan. This research uses a descriptive qualitative research approach, namely research that provides a description of factual and systematic situations and events regarding factors, as well as the relationship between phenomena. The research instruments are observation, interview and observation. The data source of this research is the results of interviews from the head of the madrasa, the deputy head of the madrasa for curriculum and teacher. The results of the study reveal that the implementation of the independent curriculum at MAN 1 Medan has been well implemented. This can be seen from the careful preparation and collaboration between various parties, including the head of the madrasa, deputy head of the madrasa from each field, teachers and other teaching staff. The involvement of all parties greatly affects the effectiveness of curriculum implementation in achieving goals effectively.